Early Growth of Breadfruit in a Variety × Environment Trial. (1st November 2019) - Lincoln, Noa Kekuewa; Cho, Alyssa; Dow, Graham; Radovich, Theodore
Abstract : Breadfruit [ Artocarpus altilis (Parkinson) Fosberg] is growing in agronomic importance throughout the global tropics as a result of its potentially high yield and nutritious, carbohydrate‐rich fruit. A bottleneck to expanded production of breadfruit is the lack of agronomic performance metrics and growth parameters, including an understanding of variety × environment interactions among commonly grown varieties. To address this knowledge gap, four varieties of breadfruit ('Otea, Fiti, Pua'a, Ma'afala) available at the commercial scale were established in a randomized complete block design at five diverse sites in Hawai'i. Soil, architectural, physiological, and climate data were collected on 18‐mo‐old trees in 2018. Growth rates varied considerably for height (0.44–2.78 m yr −1 ), diameter at breast height (0.85–5.19 cm yr −1 ), and canopy width (0.14–1.35 m yr −1 ). Diameter was significantly correlated to tree height ( r 2 = 0.88), canopy width ( r 2 = 0.83), and canopy volume ( r 2 = 0.94). Growth was significantly different between sites, and some variety × site interactions were significant. Univariate and multivariate linear regressions were used to explore relationships between growth and climate, soils, and architecture. Future work will focus on the continued evaluation of variety × environmental influence on fruit production and fruit quality and on promoting this network of sites as a valuable resource for the study of an underutilized crop species with substantial potential to be a major crop in the tropics. Core Ideas Breadfruit, while rapidly growing in importance globally, suffers from a lack of agronomic study. To our knowledge, the first variety × environment trial network of breadfruit was established in Hawai'i. Examination of initial growth rates show considerably higher rates than represented in the literature. Multiple climate and soil parameters significantly correlate to early growth.